2010
DOI: 10.1002/glia.21075
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hypothalamic degeneration in the anorectic anx/anx mouse

Abstract: Mice homozygous for the anorexia (anx) mutation are characterized by poor food intake and death by three to five weeks after birth. By P21 these mice display lower density of hypothalamic neuropeptides, including Agouti gene-related protein (AGRP). The AGRP/neuropeptide Y (NPY) system of the anx/anx mice develops normally until postnatal day (P) 12, then the normal increase in fiber density ceases, in some areas even distinctly decreases. This overlaps with activation of microglia, indicating an inflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…In addition, the canonical pathways generated in our microarray analysis suggest that cell death and inflammatory processes occur in the hypothalamus of the anx/anx mouse. This finding is in agreement with previous studies suggesting inflammation and cell death in the anx/anx hypothalamus (10,15,35,36). The anx locus is still unknown.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, the canonical pathways generated in our microarray analysis suggest that cell death and inflammatory processes occur in the hypothalamus of the anx/anx mouse. This finding is in agreement with previous studies suggesting inflammation and cell death in the anx/anx hypothalamus (10,15,35,36). The anx locus is still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, the increased hypothalamic ROS levels that we have observed in the anx/anx mouse could be causally involved in the initial starvation and anorectic phenotype of this model. In the longer perspective, a chronic overproduction of ROS could lead to the signs of oxidative stress and neuronal degeneration of both the orexigenic and anorexigenic arcuate neurons that we have previously observed in the anx/anx mouse (7,15). In addition, the canonical pathways generated in our microarray analysis suggest that cell death and inflammatory processes occur in the hypothalamus of the anx/anx mouse.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, studies have demonstrated inflammation in the hypothalamus of the anx/anx mouse (26,35,37). Taken together, these observations provide an explanation for the hypothalamic dysfunction and neurodegeneration found in anx mutant mice (38).…”
mentioning
confidence: 50%